In Quest of Wisdom; Missing Segment of Current Medicine: Wisdom; Missing Segment of Current Medicine - Abbasi, Mahmoud (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Considering the history of Islamic and Iranian culture we should represent new solutions able to join the current medicine and the former Hikmat (Wisdom) in the light of the medical world-view and through making use of the historical instructions of hikmat. Materials and Methods: In the present review study, using keywords such as Hikmat, Aristotle ethics, medical research, medical ethics as well as bioethics, we searched for the published articles and resources regarding this topic, and then they were analyzed. Ethical Considerations: Honesty in the literature and citation analysis and reporting were considered. Findings: From the old days, pious people always had sought wisdom. Medicine was considered a kind of practical wisdom that is called Pyrrhonism or wisdom and the physician was known as a pious person. A physician must reach the highest degree of knowledge so he would gain virtue. In the past, science was accompanied by the perfectness of soul and physician for achieving the truth, had to learn the medicine along with wisdom, because wisdom and medicine had a close relationship. But nowadays seems that medical science enters into the age of instability and morals in all fields have collapsed and the continuance of this process has not any bright perspective for the future of medicine. One of the obvious reasons for this situation in two recent decades is the separation between medical sciences and humanism. Conclusion: In recent decades that western world was in seek of ethics for the purpose of amends the lack of religion and virtuality in their society, we in a opposite attitude with separation of tentative science especially medicine from humanism, have caused a great and irrecoverable damages on the body of our medicine, so that unfortunately our country is following the west in this matter. The reason of this matter is in the collapse of values that was the foundation of previous wisdom, the wisdom that seems to be the missing segment of current medicine. In this article we show the necessity of attention to the medical ethics as a fundamental element in reaching the goal of medicine based on wisdom. *Corresponding Author: Mahmoud Abbasi; Email: dr.abbasi@sbmu.ac.ir; ORCID: https://orcid.org/0000-0002-4223-6818 Please cite this article as: Abbasi M. In Quest of Wisdom; Missing Segment of Current Medicine. Bioeth Health Law J. 2021; 1: 1-9 (e9). http://doi.org/10.22037/bhl.v1i1.38133